Phytochemical Test, Toxicity and Antioxidant Activity Leaves Kerehau (Callicarpa longifolia Lam.) With DPPH Method - Erwin Erwin; Redda An Nisa; Daniel Daniel (Jurnal Akta Kimia Indonesia (Indonesia Chimica Acta), 2015)
Phytochemical analysis, toxicity test by the   brine   shrimp   lethality   test   (BSLT) against Artemia salina L, and antioxidant activity evaluation of the extracts of  Kerehau leaves (Callicarpa longifolia  Lam.)  have  been  carried  out.  The  ethanol  extract  obtained  from  Kerehau  leaves  was concentrated by using a rotary vacuum evaporator. Furthermore, the crude extract was fractionated with n-hexane and ethyl acetate solvent, successively. The phytochemical  analysis of crude extract constitutes alkaloids, phenolics, flavonoids and steroids. n-hexane fraction contains alkaloids, flavonoids and steroids and ethyl acetate fraction contain alkaloids, phenolics and flavonoids. n-Hexane fraction exhibited highest toxic activity with LC50  value 90.05 ppm against Artemia salina L and ethyl acetate fraction has the highest antioxidant activity with IC50 value 38.94 ppm compared with other extracts.